Spatial heterogeneity and socio-economic correlates of unmet need for spacing contraception in India: Evidences from National Family Health Survey, 2015-16 - Margubur Rahaman; Md Juel Rana; Avijit Roy; Pradip Chouhan (Elsevier, 2022)
Background: The unmet need for spacing (UNS) is one of the key concerns of family planning programme in India despite the country achieving the replacement level of fertility. Objectives: The current study aims to identify spatial heterogeneity and factors associated with the unmet need for Spacing (UNS) in India. Data and methods: The present study used data from the National Family and Health Survey, 2015-16. The outcome variable was the unmet need for contraception for delaying subsequent births for two or more years (UNS), and the explanatory variables were socio-cultural and demographic factors. The current study included 56,742 currently married women (aged 15-49 years) who had demand for spacing during the survey. Descriptive statistics, bivariate with chi-square significance test, spatial natural break technique, and multivariate logistic regression were used to accomplish the study objectives. Results: Almost 51% of women were not using contraception to delay their next birth in India. It was found high across all socio-economic and demographic groups except higher-level education and richest groups. Spatial analysis confirms 248 districts had remarkably high UNS (68% and above). Findings of the multivariate analysis suggest women's education, autonomy, and household wealth status were important factors in reducing UNS. The likelihood of UNS was noticeably higher among women with parity three or more (AOR: 1.42 [1.3-1.55]) compared to their counterparts. Similarly, it was found 44% (AOR: 1.44[1.38-1.51]) more likely among the OBCs than the General caste. It was found 1.24 times more likely in rural (AOR: 1.24[1.19-1.30]) compared to urban. Among the geographical regions, it was found comparatively high in the South (AOR: 6.19 [5.76-6.65]) compared to other regions. Conclusion: Dealing with the UNS necessitates increasing women's education and autonomy, planning to make client choice-based services more accessible, and promoting birth-spacing focused family planning policies.